Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) Kurikulum Merdeka di SMA Negeri 1 Praya Tengah - Lilis Lestari; Siti Rohana Hariana Intiana; Pipit Aprilia Susanti (Mataram University, 2026)
The implementation of the Merdeka Curriculum through the Pancasila Student Profile Strengthening Project (P5) is one of the efforts to develop students’ character and competencies based on the values of Pancasila. In Indonesian language instruction at the high school level, the P5 theme “Nurturing Mind and Body” is expected to support students in developing character, collaboration skills, responsibility, and self-awareness through project-based learning activities.This study aims to identify the implementation of the Pancasila Student Profile Strengthening Project (P5) in Indonesian language instruction at Senior High Schools (SMA) with the theme “Nurturing Mind and Body.” This study employs a descriptive qualitative method. Data were collected through interviews with the vice principal for curriculum and Indonesian language teachers, observations, and documentation of P5 implementation activities. Data analysis techniques included data reduction, data presentation, and drawing conclusions.The research findings indicate that the planning phase included forming a team of facilitators, assessing school readiness, determining themes and subthemes, developing modules, and planning project reporting strategies. During implementation, learning activities utilized textbooks and the Merdeka Belajar platform website. Although some activities were not fully carried out in accordance with the modules, the project proceeded effectively. Evaluation included reflection activities, feedback, and assessment management. Overall, this implementation supports character development and learning outcomes.